Physical activity when riding an electric-assisted bicycle with and without cargo - Martnes, Jørgen Jerstad; Bere, Elling (Frontiers in Sports and Active Living, 2023)
Background: Regular physical activity provides several health benefits, and active transport is a convenient way to implement physical activity in everyday life. However, bikes' lack of possibilities to carry cargo is a limitation. E-cargo bikes can help overcome barriers to cycling and increase levels of active transport while still providing the option to carry cargo such as groceries and children. As such, e-cargo bikes have a greater potential for being a substitute for cars, but relevance is not known as no study has assessed the energy expenditure and time used using e-cargo bikes with considerable cargo.The aim of this study is to compare time spent riding and exercise intensity when 1) riding an electric-assisted bicycle with cargo (30 kg) and without cargo and 2) compared to driving a car.This study has a randomised crossover design. Eleven participants (6 women) were recruited through convenience sampling. The participants traversed through a 4.5 km route with three different forms of transportation: an E-bike with 30 kg cargo, an E-bike without cargo and a car. Oxygen uptake was measured with a portable oxygen analyser (Metamax 3B), and time spent cycling was measured on site by the test leader using a stopwatch.Riding the E-bike with cargo was slightly slower than riding the E-bike without cargo (11.8 min vs 11.1 min, p=0.017) and driving the car (8.8 min, p=0.002). There was no significant difference in exercise intensity between E-bike with and without cargo but riding the E-bike with cargo entailed significantly higher exercise intensity compared to driving the car (4.9 METs vs 1.4 METs, p=<0.001).Conclusions: E-biking with cargo was rather similar in time spent and exercise intensity to e-biking without cargo, and not much slower than driving a car. Using e-cargo bikes, therefore, appears as a good alternative to driving a car when in need of carrying things such as grocery bags and children; resulting in increasing physical activity and, at the same time, decreasing greenhouse gas emissions.